(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This paper establishes an analog of the well-known theorem of P. J. Bickel and J. A. Yahav on the number of exits of a multidimensional random walk from expanding sets. This theorem and related problems are carried forward for the moment of the first exit.